2019
DOI: 10.1016/j.whi.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Pregnancy and Contraceptive Use: An In-Depth Study of Women in Los Angeles Methadone Clinics

Abstract: Introduction: In 2016, 2.1 million people in the United States were estimated to have an opioid use disorder. While the disorder can be safely and effectively treated with prescription methadone, treatment is potentially long-term and may span women's peak childbearing ages. Little is known about women's reproductive health needs while on methadone. Methods: We interviewed 22 sexually active, non-pregnant women ages 21-39 at two Los Angeles methadone clinics in 2016. The interviews were transcribed and coded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…23 Low uptake of contraception in opioid using women has been attributed to numerous factors, including poor postpartum visit attendance, 3,24,25 stigma and fear of losing custody of their child(ren), 26 lack of information regarding both LARCs and short-acting methods, 27 and misunderstanding of their fertility. 3,28 Interestingly, we also found that more than half of women with self-reported opioid use in our study chose immediate tier 1 method uptake, of which Data are represented as n (%), unless noted as means in which case it is meanstandard deviation. a Tier 1 contraceptive methods according to the WHO classification 13,14 : female/male sterilization, intrauterine device, and contraceptive implant.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…23 Low uptake of contraception in opioid using women has been attributed to numerous factors, including poor postpartum visit attendance, 3,24,25 stigma and fear of losing custody of their child(ren), 26 lack of information regarding both LARCs and short-acting methods, 27 and misunderstanding of their fertility. 3,28 Interestingly, we also found that more than half of women with self-reported opioid use in our study chose immediate tier 1 method uptake, of which Data are represented as n (%), unless noted as means in which case it is meanstandard deviation. a Tier 1 contraceptive methods according to the WHO classification 13,14 : female/male sterilization, intrauterine device, and contraceptive implant.…”
Section: Discussionmentioning
confidence: 66%
“… 23 Low uptake of contraception in opioid using women has been attributed to numerous factors, including poor postpartum visit attendance, 3 , 24 , 25 stigma and fear of losing custody of their child(ren), 26 lack of information regarding both LARCs and short-acting methods, 27 and misunderstanding of their fertility. 3 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…7 Attitudes were similar among teenagers who used intravenous drugs and adults who used methadone, as contraceptive use decreased when they perceived they were in stable or longer-term sexual relationships. 17,28 Additionally, women may choose not to use contraception because of previous adverse experiences with contraception or a desire for pregnancy.…”
Section: Factors Affecting Contraceptive Accessmentioning
confidence: 99%
“…One study found that over one‐third of women surveyed stated they would not use any form of contraception with a monogamous partner, whereas women in new relationships were more likely to use external condoms 7 . Attitudes were similar among teenagers who used intravenous drugs and adults who used methadone, as contraceptive use decreased when they perceived they were in stable or longer‐term sexual relationships 17,28 . Additionally, women may choose not to use contraception because of previous adverse experiences with contraception or a desire for pregnancy.…”
Section: Factors Affecting Contraceptive Accessmentioning
confidence: 99%
See 1 more Smart Citation